The impact of moral education on social welfare as a governmental policy - Eirini Leriou; Anastasios Tasopoulos (European Regional Science Association (ERSA), 2015)
All the progress made by the economists who established the theory of welfare, are based on the needs for the progress in engineering that marked out the era of the industrial revolution. All the models that go along with these theories are based on the science of engineering and contributed at the same time to its flourishing. We realize that these theories were derived from the scientific field of engineering, in order to promote the development of engineering and beyond this the industrial revolution. The economic crisis is global and reflects the moral swamp that mankind has created. The current economic climate dictates a review of the theory of welfare and its reconciliation on a fundamentally different basis. The global economic climate has shifted the need for advances in engineering of earlier periods to the need for establishing moral values . Any theory or formulation of welfare must sustain the todays requirement of moral values. Moral values can be retrieved only through moral education and only in Aristotle we can find what ethics and moral education are. Therefore, todays need is to work on moral education. In this paper we investigate the impact of moral education in welfare in a case study referring to Greece. On this basis a function is produced examining whether general overall welfare improves or worsens through today's education. This equation is useful as it recommends to the decision makers to put emphasis on moral education.
Keywords: 330; welfare model; social welfare; ethics education; crisis; policy